Conservative Treatment of Iatrogenic Ascending Aortic Hematoma Post-Rotablator Coronary Procedure - Doutriaux, Maxime; Pariente, Benjamin; Zahnan, Jad; Marchand, Xavier (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Background Aortic intramural hematoma due to coronary artery dissection is a rare and serious complication during percutaneous coronary intervention.Case Presentation A 78-year-old female patient was admitted for diagnostic coronarography in the context of stable angina. The coronarography showed an asymmetric and significate calcification in the ostium of the right coronary requiring Rotablator (Boston Scientific) procedure complicated by iatrogenic ascending aortic hematoma. After surgical advice, a conservative approach was decided with total hematoma resorption and recovery 1 week later.Conclusion With stable patient, conservative treatment may be suitable after aortic hematoma due to coronary dissection.
Keywords: aortic disease; imaging; aorta; percutaneous coronary intervention